Comprehensive miRNome-Wide Profiling in a Neuronal Cell Model of Synucleinopathy Implies Involvement of Cell Cycle Genes - Findeiss, Elisabeth; Schwarz, Sigrid C.; Evsyukov, Valentin; Rösler, Thomas W.; Höllerhage, Matthias; Chakroun, Tasnim; Nykänen, Niko-Petteri; Shen, Yimin; Wurst, Wolfgang; Kohl, Michael; Tost, Jörg; Höglinger, Günter U. (Frontiers in Cell and Developmental Biology, 2021)
Growing evidence suggests that epigenetic mechanisms like microRNA-mediated transcriptional regulation contribute to the pathogenesis of parkinsonism. In order to study the influence of microRNAs, we analyzed the miRNome two days prior to major cell death in α-synuclein-overexpressing Lund human mesencephalic neurons, a well-established cell model of Parkinson’s disease, by next-generation sequencing. The expression levels of 23 microRNAs were significantly altered in α-synuclein-overexpressing cells, 11 were down- and 12 upregulated (P < 0.01). The in silico analysis of known target genes of these microRNAs was complemented by the inclusion of a transcriptome dataset of the same cellular system, revealing the G0/G1 cell cycle transition to be markedly enriched. Out of 124 KEGG-annotated cell cycle genes, 15 were present in the miRNA target gene dataset and 10 were found to be significantly altered upon α-synuclein overexpression, with 8 genes up- (CCND1, CCND2, CDK4, TGFB1, TP53 at P < 0.01; E2F3, MYC, SMAD3 at P < 0.05) and 2 genes downregulated (CDKN1C, MDM2 at P < 0.001). Additionally, several of these altered genes are targeted by miRNAs hsa-miR-34a-5p and hsa-miR-34c-5p, which also modulate α-synuclein expression levels. Functional intervention by siRNA-mediated knockdown of the cell cycle gene cyclin D1 (CCND1) confirmed that silencing of cell cycle initiation is able to substantially reduce α-synuclein-mediated cytotoxicity. The present findings suggest that α-synuclein accumulation induces microRNA-mediated aberrant cell cycle activation in post-mitotic dopaminergic neurons. Thus, the mitotic cell cycle pathway at the level of microRNAs might offer interesting novel therapeutic targets for Parkinson’s disease.